Depression, anxiety, and the COVID-19 pandemic: Severity of symptoms and associated factors among university students after the end of the movement lockdown. - Luke Sy-Cherng Woon; Mohammad Farris Iman Leong Bin Abdullah; Hatta Sidi; Nor Shuhada Mansor; Nik Ruzyanei Nik Jaafar (PLoS ONE)
Background and aims This online cross-sectional study investigated the severity of depressive, anxiety, and stress symptoms among university students and determined the association between various factors and the levels of depressive and anxiety symptoms in response to the coronavirus disease 2019 (COVID-19) pandemic after the movement control order (MCO) was lifted. Methods A total of 316 participants were administered a self-report questionnaire that collected data on sociodemographic attributes, personal characteristics, COVID-19-related stressors, religious coping, and clinical characteristics. In addition, the Multidimensional Scale of Perceived Social Support (MSPSS) and the 21-item Depression, Anxiety and Stress Scale (DASS-21) were administered. Results Regarding depression, 15.5%, 11.7%, and 9.2% of the participants reported mild, moderate, and severe to extremely severe depression, respectively. For anxiety, 7.0%, 16.5%, and 13.2% of the respondents had mild, moderate, and severe to extremely severe anxiety, respectively. Moreover, 26.3% of participants had mild stress, 9.5% had moderate stress, and 6.6% had severe to extremely severe stress. The multiple linear regression model revealed that frustration because of loss of daily routine and study disruption and having preexisting medical, depressive, and anxiety disorders were associated with elevated depressive symptoms, while a greater degree of family and friends social support was associated with less depressive symptoms after adjusting for age, gender, and marital status. It was also found that frustration because of study disruption and having preexisting medical, depressive, and anxiety disorders were associated with elevated anxiety symptoms, while being enrolled in medicine-based courses and having a greater degree of family support were factors associated with less anxiety symptoms after adjusting for age, gender, and marital status. Conclusion There is a need to conduct a longitudinal study in the future to confirm the causal relationship between the significant predictive factors and depression and anxiety identified in this study, and maintenance of a persistent flow of academic activities and social interaction may be of utmost importance to safeguard the mental wellbeing of university students.